Nematicidal Constituents from the Essential Oil of Chenopodium Ambrosioides Aerial Parts - Chuan Qi Bai; Zhi Long Liu; Qi Zhi Liu (E-Journal of Chemistry)
Essential oil of Chinese medicinal herb, Chenopodium ambrosioides aerial parts was found to possess nematicidal activity against the root-knot nematodes, Meloidogyne incognita. The essential oil of C. ambrosioides was obtained by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 27 components of the essential oil were identified. The principal compounds in C. ambrosioides essential oil were (Z)-ascaridole (27.27%), ρ-cymene (19.05%), isoascaridole (14.75%), α-pinene (6.33%) and α-terpinene (5.12%). Bioactivity-guided chromatographic separation of the essential oil on repeated silica gel columns led to isolate three volatile components ((Z)-ascaridole, ρ-cymene and isoascaridole) from the essential oil. The essential oil and (Z)-ascaridole exhibited strong nematicidal activity against M. incognita with LC50 values of 49.55 μg/mL and 32.79 μg/mL, respectively. ρ-Cymene and isoascaridole also possessed nematicidal activity against M. incognita with LC50 values of 435.89 μg/mL and 1323.51 μg/mL, respectively but weaker than the crude essential oil.